Developing Community-Based Mentorship: Supporting Health Science Training in Historically Marginalized Communities. - Elias, Thistle I.; Thompson, Jessica R.; Boak, Brandi; Cannon, Joy (Health Promotion Practice, 2022)
Community mentors can play a unique and critical role in developing and supporting graduate and health professional student learning in underresourced community-based settings. These mentors can benefit from extra preparation for a potentially unfamiliar role as teachers about complex social and structural challenges faced by the populations with which they work. Encouraging mentors to recognize and share their valuable expertise while developing their teaching skills can (1) improve mentors' abilities to work effectively with graduate-level and health science students from multiple disciplines, (2) bolster student learning about important historical social and structural determinants of participants' health, and (3) help students understand the broader context within which organizations serving vulnerable populations operate. As such, in one full-time, community-engaged, interdisciplinary practicum program, Bridging the Gaps-Pittsburgh, part of the multiinstitutional Bridging the Gaps Network, a half-day mentor workshop has been required for two decades for new community mentors to develop their capacity to be community-based teachers of largely graduate-level health science students. Additionally, program staff aim to support mentors and connect them to faculty and community resources in a variety of ways. Our model supports the argument that applied learning by health professional students in community settings can be significantly enhanced through building and supporting the capacity of community mentors to act as recognized teachers in areas of community expertise.